Sherlock Holmes and the Biopolitics of the Fantastic - Jukić, Tatjana (2012)
The Sherlock Holmes narratives seem to want to dispense with the fantastic – with what Conan Doyle, in his first Sherlock Holmes case, A Study in Scarlet, describes as necromancy. Or: they seem organized around the effort to revise the very condition of the fantastic by relegating it to the realm of phantasm, illusion or incomplete analysis. It is here already that Conan Doyle proposes in fact that his late Victorian detective fiction be approached from what at that point was only to form as psychoanalysis. Indeed, Sherlock Holmes emerges as downright fantastic himself precisely where he manages to expose the fantastic as the phantasmatic or else as the underanalyzed. A Study in Scarlet provides also the position where such an approach to the fantastic hinges on the clinical, just as psychoanalysis depends on the point of contact of the critical and the clinical. It introduces Dr. Watson as the chronicler of the Holmes cases and the principal instance where the Holmes narratives are pieced together, so that Holmes comes into being always already contaminated with the knowledge of pathology. Further, Dr. Watson is shown to have met Holmes with his health “irretrievably ruined” because of the wound he had sustained in the Second Afghan War and typhoid he there contracted. Watson, the very instance where the Holmes narratives are assembled, shows therefore as irretrievably punctured, perforated and humoral: as comparable in fact to Deleuze's and Guattari’s description of the “body without organs.” Also, pathology and the critical are tied up for Watson with his account of the war, which means that the very emergence of the narrative voice in Conan Doyle is implicated in biopolitics. (Not to mention Conan Doyle’s lifelong interest in the study of warfare.) Consequently, if the main interest of the Holmes narratives is the reassignment of the fantastic which anticipates psychoanalysis, both the reassigned fantastic and the adumbrated psychoanalysis show in Conan Doyle as biopolitical concerns. The positions that I would like to explore in my lecture are therefore the following: what happens to the narrative which imagines its voice as that of medical knowledge in search of psychoanalysis? What happens to the literary fantastic once it gets mobilized as integral to this process? What if murder is the only crime adequate to the imaginary of detective fiction? Could it be that all other crimes, in detective fiction, are but inadequate substitutes for this originary biopolitical phantasm? Can detective fiction be taken up as the privileged position where the fantastic gets mobilized as the phantasmatic? Also: is not (late Victorian) detective fiction, for this reason, the privileged place from where to approach the biopolitical implications of the fantastic?